Job Satisfaction of Faculty Members of State Universities and Colleges (SUCs) in Bicol, Philippines - Bongalonta, Michael B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study determined the demographic profile of faculty members of State Universities and Colleges in Bicol, Philippines and assessed their job satisfaction. This also aimed to test if there is significant difference in the extent of the job satisfaction of faculty members with respect to their demographic profile when grouped according to gender, age, length of service, status of appointment and educational attainment. Descriptive method of researcher was utilized to realize the objectives of this study. Data were collected through the use of a modified survey questionnaire which was tested for validation and reliability using Cronbach’s value. To facilitate the analyses and interpretations of the data gathered, descriptive statistics (frequency count, ranking and percentage technique) and inferential statistics (one-way ANOVA) were used and made easier through the aid of the Statistical Packages for the Social Science (SPSS). As a result, it was concluded that State Universities and Colleges in the Province of Bicol Philippines (SUCs) are equally represented with new and senior faculty members in terms of number of years in service who have met and complied with the academic requirements of the Civil Service Commission and that most of them are permanent and with security of tenure in the College or University where they are in. Bicol SUC faculty members are highly satisfied with their job and it was found out that the extent of overall job satisfaction of the faculty members in Bicol SUCs does not differ with respect to their demographic profile.